Wemberly worried - Henkes, Kevin (New York : Scholastic, 2001)
A mouse named Wemberly, who worries about everything, finds that she has a whole list of things to worry about when she faces the first day of nursery school.
Originally published: New York : Greenwillow Books, 2000.
170
Keywords: Children's literature; Worry -- Fiction; First day of school -- Fiction; Nursery schools -- Fiction; Schools -- Fiction; Mice -- Fiction